Sutureless bioprosthesis for aortic valve replacement: surgical and clinical outcomes - Ferreira, Ricardo (2022)
© 2022 The Authors. Journal of Cardiac Surgery published by Wiley Periodicals LLC. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.